A SURVEY OF HEALTHCARE ACCESS AND UTILIZATION IN SELECTED RURAL AND URBAN SETTLEMENT OF PLATEAU STATE, NIGERIA - Fulus, Daniel Fom (FUDMA Journal of Sciences, 2025)
This study examines disparities in healthcare access and utilization between rural and urban communities in Plateau State, Nigeria. Using a cross-sectional survey design, data were collected from 384 respondents across six selected local government areas (LGAs). Fisher’s Discriminant Analysis was employed to identify significant factors influencing healthcare access. The results demonstrate that rural residents face greater challenges, including long travel distances to health facilities, inadequate transportation, financial constraints, and low health insurance coverage. Maternal and child healthcare utilization is also lower in rural areas, contributing to higher under-five mortality rates. The study finds that educational status and proximity to health facilities are critical determinants of healthcare access. The use of Fisher’s Discriminant Analysis proves appropriate, as it effectively differentiates between rural and urban healthcare accessibility based on key variables, achieving a classification accuracy of 67.7%. This validates its suitability in modelling healthcare disparities. The study highlights the need for strategic policy interventions, including expanding rural healthcare infrastructure, subsidizing healthcare costs, and increasing health awareness programs. Addressing these disparities is essential to achieving universal health coverage and improving public health outcomes in Plateau State.